The Self-Appointed Jury: Punitive Sentiment And Prosocial Aggression In Christie’s Orient Express - Donny Syofyan (Universitas Muara Bungo, 2025)
This study presents a biocultural analysis of Agatha Christie’s Murder on the Orient Express (1934) through the theoretical lens of Literary Darwinism. While traditional scholarship often focuses on the novel’s formalist